Optimalisasi Prinsip-Prinsip Pengelolaan Sarana dan Prasarana dalam Mutu Pembelajaran di Madrasah - Dewy Rismayanti; Husni Idris; Muthia Umi Setyoningrum (Faculty of Education and Teacher Training of UINSI Samarinda, 2026)
Abstract Improving the quality of learning is becoming increasingly important in the modern era. One aspect that influences learning quality is the availability of facilities and infrastructure. However, suboptimal management of facilities and infrastructure and a lack of attention to the principles of facility and infrastructure management often hamper the learning process. This study aims to analyze the optimization of facility and infrastructure management principles in improving learning quality at Darussalam Samarinda Islamic Junior High School (MTs). This research is descriptive and uses a qualitative approach. Data were collected through interviews, document analysis, and observations. Data sources consisted of the madrasah principal, students, teachers, and the deputy principal for facilities and infrastructure. This study shows that improving the quality of learning can be done by applying the principles of optimal facility and infrastructure management, including: 1) the principle of achieving goals by providing infrastructure that supports learning objectives, 2) the principle of efficiency carried out starting from the maturity of planning and optimal use and maintenance of facilities and infrastructure, 3) administrative principles through the provision of infrastructure according to quality standards, 4) clarity of responsibility with the division of roles and tasks to teachers, and 5) the principle of cohesiveness through coordination, cooperation, and participation of all parties. This study shows that the quality of learning in madrasas can be achieved through optimizing the principles of facility and infrastructure management optimally. This is a practical study that educational institutions need to design facility management strategies to meet learning objectives. Keywords: Quality of Learning, Principles, Facilities and Infrastructure Management Abstrak Peningkatan mutu pembelajaran menjadi semakin penting di era modern. Salah satu aspek yang mempengaruhi mutu pembelajaran adalah ketersediaan sarana dan prasarana. Namun pengelolaan sarana dan prasarana yang belum optimal dan tidak memperhatikan prinsip-prinsip manajemen sarana dan prasarana sering menghambat proses pembelajaran. Studi ini bertujuan menganalisis optimalisasi prinsip-prinsip pengelolaan sarana dan prasarana dalam mutu pembelajaran di Madrasah Tsanawiyah (MTs) Darussalam Samarinda. Penelitian ini berjenis deskriptif dan menggunakan pendekatan kualitatif. Data penelitian dikumpulkan melalui wawancara, analisis dokumen, dan pengamatan. Sumber data terdiri dari kepala madrasah, siswa, guru, dan wakil kepala bidang sarana dan prasarana. Penelitian ini menunjukan hasil bahwa peningkatan mutu pembelajaran dapat dilakukan salah satunya dengan menerapkan prinsip prinsip pengelolaan sarana dan prasarana yang optimal, meliputi: 1) prinsip pencapaian tujuan dengan menyediakan sarana prasarana yang mendukung tujuan pembelajaran, 2) prisnip efisiensi yang dilakukan mulai dari kematangan perencanaan serta penggunaan dan pemeliharaan sarana dan prasarana yang optimal, 3) prinsip administratif melalui penyediaan sarana prasarana sesuai standar mutu, 4) kejelasan tanggung jawab dengan pembagian peran maupun tugas kepada guru, dan 5) prinsip kekohesifan melalui koordinasi, kerja sama, dan partisipasi seluruh pihak. Studi ini memperlihatkan bahwa mutu pembelajaran di madrasah dapat dicapai melalui optimaliasi prinsip-prinsip pengelolaan fasilitas dan infrastrutur secara optimal. Hal ini menjadi kajian praktis bahwa lembaga pendidikan perlu merancang strategi pengelolaan fasilitas untuk memenuhi tujuan pembelajaran. Kata Kunci: Mutu Pembelajaran, Prinsip-Prinsip, Pengelolaan Sarana dan prasarana